2015
DOI: 10.1097/cej.0000000000000119
|View full text |Cite
|
Sign up to set email alerts
|

Fruit and vegetable consumption and risk of bladder cancer

Abstract: This meta-analysis was conducted to assess the association between fruit and vegetable intake and bladder cancer risk. Eligible studies published up to August 2014 were retrieved both through a computer search of PubMed, Embase and the Cochrane library and through a manual review of references. The summary relative risks with 95% confidence intervals (CIs) for the highest versus the lowest intakes of fruits and vegetables were calculated with random-effects models. Heterogeneity and publication bias were also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 46 publications
0
18
1
2
Order By: Relevance
“…We measured lower levels of avocadyne 4-acetate and 1-acetoxy-2-hydroxy-16-heptadecen-4-one in the urine from patients with NMIBC than in the urine from healthy controls. Both of these metabolites are members of the class of compounds known as long-chain fatty alcohols, which are present in fruits, supporting the impact of dietary habits on BC ( 27 , 28 ).…”
Section: Discussionmentioning
confidence: 70%
“…We measured lower levels of avocadyne 4-acetate and 1-acetoxy-2-hydroxy-16-heptadecen-4-one in the urine from patients with NMIBC than in the urine from healthy controls. Both of these metabolites are members of the class of compounds known as long-chain fatty alcohols, which are present in fruits, supporting the impact of dietary habits on BC ( 27 , 28 ).…”
Section: Discussionmentioning
confidence: 70%
“…The role of diet on bladder carcinogenesis may be mediated by many metabolites of foods, which are excreted through the urinary tract. Previous studies—although not all—on bladder cancer have shown a protective role of high intakes of fruit and vegetables and selected nutrients related to these foods [ 11 , 37 ]. A favorable effect on bladder cancer of olive oil has also been suggested [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Total participants 56 005 (9) 64 866 (11) 49 457 825 268 445 204 (8) 37 102 (6) 33 856 (6) 40 782 749 328 (8) 75 035 (13) 5632 138 263 6 33 856 825 343 626 782 752 559 (13) 2580 122 465 6 152 4303 9248 7940 (27) 520 15378 (11) 3538 ( approximately three pieces of fruit), using the lowest intake category as a reference. Fruit types (citrus fruits, soft fruits, stone fruits, tropical fruits, pome fruits and fruit products) were each analysed as a continuous variable per 25 g of fruits per day increase and were modelled into quartiles, using the lowest quartile as a reference.…”
Section: Discussionmentioning
confidence: 99%